Psychological Safety as a condition for development of a microenterprise - Tomasz Balicki; Krzysztof Leja (Journal of Modern Science)
Objective: The objective of this article is to demonstrate the importance of psychological safety as a condition for the development of a selected microenterprise in Poland. The article analyses how psychological safety influences increased effectiveness and employee engagement in the selected microenterprise. Material and Method: The subject of the study is a microenterprise in the consulting industry in Poland. The article adopts a qualitative approach using participatory observation. Elements of organizational knowledge management theory were utilized to describe the selected organization. Psychological safety in the selected organization was assessed, and the results were applied to the Wise Compassion Matrix. Results: The microenterprise successfully implements the SECI model as part of its organizational knowledge management, which in practice means the effective use of its most important asset, knowledge. It was demonstrated that a high level of psychological safety promotes motivation and engagement among the employees of the studied company, while also recognizing the potential for further improvement. Conclusions: A high level of psychological safety is associated with wise compassion from management and positively influences employee functioning and engagement in the microenterprise. The results of the psychological safety assessment allowed for the identification of critical areas requiring improvement. While the results do not allow for generalizations, they can serve as a basis for exploring other organizations, regardless of the industry.